Establishment and characterization of a prostate cancer cell line from a prostatectomy specimen for the study of cellular interaction. Issue 8 (10th May 2019) - Wang, Ruoxiang; Chu, Gina C.‐Y.; Wang, Xudong; Wu, Jason B.; Hu, Peizhen; Multani, Asha S.; Pathak, Sen; Zhau, Haiyen E.; Chung, Leland W.K.
Abstract : Though human prostate cancer (PCa) heterogeneity can best be studied using multiple cell types isolated from clinical specimens, the difficulty of establishing cell lines from clinical tumors has hampered this approach. In this proof‐of‐concept study, we established a human PCa cell line from a prostatectomy surgical specimen without the need for retroviral transduction. In a previous report, we characterized the stromal cells derived from PCa specimens. Here, we characterized the epithelial cells isolated from the same tumors. Compared to the ease of establishing prostate stromal cell lines, prostatic epithelial cell lines are challenging. From three matched pairs of normal and tumor tissues, we established one new PCa cell line, HPE‐15. We confirmed the origin of HPE‐15 cells by short tandem repeat microsatellite polymorphism analysis. HPE‐15 cells are androgen‐insensitive and express marginal androgen receptor, prostate‐specific antigen and prostate‐specific membrane antigen proteins. HPE‐15 expresses luminal epithelial markers of E‐cadherin and cytokeratin 18, basal cell markers of cytokeratin 5 and p63 and neuroendocrine marker of chromogranin A. Interestingly, HPE‐15 Cells exhibited no tumorigenicity in different strains of immune‐deficient mice but can become tumorigenic through interaction with aggressive cancer cell types. HPE‐15 cells can thus serve as an experimental model for the study of PCa progression, metastasis and tumor cell dormancy. Abstract : What's new? Though human prostate cancer (PCa) heterogeneity can best be studied using multiple cell types isolated from clinical specimens, the difficulty of establishing cell lines and need for genetic manipulation have hampered this approach. This article describes the establishment and characterization of an epithelium‐like cell line from a prostatectomy specimen without exogenous gene transfer. Not in itself tumorigenic, this new cell line can become highly tumorigenic via cell–cell interaction with aggressive prostate cancer cells. This newly established cell line is thus an ideal model for investigating the mechanism of prostate cancer progression and metastasis.